2014
DOI: 10.1016/j.redox.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Brain mitochondria from DJ-1 knockout mice show increased respiration-dependent hydrogen peroxide consumption

Abstract: Mutations in the DJ-1 gene have been shown to cause a rare autosomal-recessive genetic form of Parkinson’s disease (PD). The function of DJ-1 and its role in PD development has been linked to multiple pathways, however its exact role in the development of PD has remained elusive. It is thought that DJ-1 may play a role in regulating reactive oxygen species (ROS) formation and overall oxidative stress in cells through directly scavenging ROS itself, or through the regulation of ROS scavenging systems such as gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 47 publications
2
37
1
1
Order By: Relevance
“…DJ‐1 is localized to mitochondria as a constituent of the thioredoxin/apoptosis signal‐regulating kinase 1 (Trx/Ask1) complex, which can modulate the elimination of endogenous ROS . DJ‐1 deficiency will result in H 2 O 2 accumulation in brain mitochondria, elevated oxidative stress level, and death of DA neurons …”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…DJ‐1 is localized to mitochondria as a constituent of the thioredoxin/apoptosis signal‐regulating kinase 1 (Trx/Ask1) complex, which can modulate the elimination of endogenous ROS . DJ‐1 deficiency will result in H 2 O 2 accumulation in brain mitochondria, elevated oxidative stress level, and death of DA neurons …”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Očigledno je da AGM pokazuje protektivne efekte u odnosu na ćelijsku membranu samo u prisustvu oksidativnog stresa, u ovom slučaju izazvanog HPZ. To bi ukazivalo da se aktivacija procesa peroksidacije kod primene AGM ne odvija preko NO, već preko drugog mogućeg puta, a to je formiranje OH Uloga glutationa u zaštiti ćelija od toksičnih dejstava SR i drugih komponenata sa elektrofilnim svojstvima ogleda se u njegovom antioksidativnom dejstvu, jer neutrališe RVK unutar ćelije direktno ili preko ciklusa GPx/glutation (50,51). Povećanje nivoa ukupnog glutationa u kori prednjeg mozga 24 h posle trovanja HPZ je, uzevši u obzir njegovo antioksidativno dejstvo, rezultat aktivacije protektivnih mehanizama moždanog tkiva u ovim uslovima (Slika 3A).…”
Section: Diskusijaunclassified
“…The complex I defect could be the reason of the increased ROS production detected in patient fibroblasts at the basal conditions; in addition these cells showed, similar to what has been reported in the knockdown or knockout DJ‐1 cell models , a higher sensitivity to oxidative stress, displaying under stress conditions a dramatic increase in ROS production compared to control cell lines. Moreover, the increased oxidative stress was underlined by the high concentrations of GSSG and the altered GR activity in patient blood, resembling what has been found in brain mitochondria of DJ‐1 −/− knockout mice . It has been shown that DJ‐1 upregulates GSH synthesis to reduce ROS level during oxidative stress stimulating the expression of both SOD and glutamate cysteine ligase genes by an unknown mechanism .…”
Section: Discussionmentioning
confidence: 99%